Optimal control of transverse vibration of Euler-Bernoulli beam with multiple dynamic vibration absorbers using Taguchi’s method - Khang, Nguyen Van; Phuc, Vu Duc; Huong, Nguyen Thi Van; Duong, Do The (Vietnam Journal of Mechanics, 2018)
Vibration absorbers are frequently used to suppress the excessive vibrations in structural systems. In this paper, an imposing nodes technique is applied for vibration suppression of Euler-Bernoulli beams subjected to forced harmonic excitations by means of multiple dynamic vibration absorbers. A procedure based on Taguchi’s method is proposed to determine the optimum absorber parameters to suppress the vibration amplitude of the beams. Numerical tests are performed to show the effectiveness of the proposed procedure.